2021
DOI: 10.1515/htm-2020-0007
|View full text |Cite
|
Sign up to set email alerts
|

Sinter Hardening PM Steels Prepared through Hybrid Alloying

Abstract: In powder metallurgy (PM), there are several ways of introducing alloying elements into a PM material in order to adjust a certain alloying element content. Each alloying route has its advantages and disadvantages. Master alloys (MA), powders with a high content of typically several alloying elements, can be added in small amounts to a base powder, especially to introduce oxygen sensitive elements such as Cr, Mn, and Si. In addition, the master alloy can be designed in such a way that a liquid phase is formed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…The martensite start (Ms) temperature is affected by the C content and the alloying elements distributed in the material. In a previous study [26], the measured Ms temperatures were shown to be in good agreement with Steven and Haynes' calculations [27] for Ms. This means that if deviations between the measured and the calculated Ms temperature occur, remaining MA particles might be an explanation for this case, since they "trap" alloying elements and C away from the materials matrix which are subsequently not available for hardening.…”
Section: Hardenability Of Samples Sintered At 1180 • C With 10 K/min Heating Ratesupporting
confidence: 75%
“…The martensite start (Ms) temperature is affected by the C content and the alloying elements distributed in the material. In a previous study [26], the measured Ms temperatures were shown to be in good agreement with Steven and Haynes' calculations [27] for Ms. This means that if deviations between the measured and the calculated Ms temperature occur, remaining MA particles might be an explanation for this case, since they "trap" alloying elements and C away from the materials matrix which are subsequently not available for hardening.…”
Section: Hardenability Of Samples Sintered At 1180 • C With 10 K/min Heating Ratesupporting
confidence: 75%
“…Also, the masteralloy route, e.g. as ferroalloys or as complex carbidic masteralloys has been regarded as an option [8][9][10], in particular, since new atomising techniques can yield high output of fine, rounded particles [11][12][13][14]. On the other hand, adding Cr as elemental alloying particles has not been studied too frequently, although the mechanical properties reported are quite attractive [15].…”
Section: Introductionmentioning
confidence: 99%